Animal flocking behaviours in game development using FAME - Tan, Weisheng (2015)
As technologies continue to advance rapidly, the demand for more complex and realistic video games is growing fast as well. One crucial ingredient in making modern games feel more realistic is the artificial intelligence, particularly swarming intelligence. So, by having a comprehensive library that provides dynamic swarm control, game developers will be able to create realistic games very quickly and easily, which is what the Flocking Animation Modeling Environment (FAME) delivers. This project is divided into two parts. The first part focuses on improving the usability of an existing application, called FameDemo, by revamping its user interface. As its name implies, FameDemo was built to demonstrate the capabilities of FAME. The second part is the development of a game called Space Hurdle. The emphasis of this part of the project is to highlight the benefits of using FAME in the development of a game. Throughout the development of Space Hurdle, the benefits of FAME were very obvious. By utilizing it, the movements of the AI agents in the game were programmed in very easily and quickly, which sped up the entire development process significantly. Although the game turned out great, it would be more ideal if it is ported to mobile devices as such Android or iOS because of the simple gameplay and the old school arcade theme.